Fatal, Fulminant Herpetic Tracheobronchitis following Cardiac Surgery. (25th May 2018) - Vaideeswar, Pradeep; Marathe, Supreet P
Abstract: Nosocomial infection is a feared complication after any surgical procedure. Respiratory tract microbial colonization and development of ventilator-associated tracheobronchitis and/or pneumonia are unfortunate sequelae in mechanically ventilated patients, commonly caused by bacteria; viral etiology is seldom anticipated. We present a fatal case of fulminant herpetic tracheobronchitis in a 33-month-old patient following cardiac surgery. We intend to highlight the fact that herpetic viral etiology should be considered in post-operative respiratory infections.